Analyze The Causes of The Russian-Ukraine War with Waltz's Three Images (Individual, Domestic Politics, International System) - Mohammad Rubel; Md Sazzad Hossain (Journal of Social Science, 2022)
No one is calling the Russia-Ukraine conflict is considered the commencement of World War III right now. But all analyzes see it as Europe's biggest conflict since World War II as the war dragged on and it assumed a different character as well. The opening weeks of Russia's invasion of Ukraine were a war of military strategy. On the other hand, the Ukrainian troops-built resistance was necessary to stop the enemy's advance. In military strategy, a well-trained and efficient army is necessary to conduct war properly. Over the past six years, with the help of Western allies, Ukraine has been able to build a military capable of such a war. As part of such a war, where resistance is needed (such as in Kyiv), the Ukrainian military has done so. Again, the army has withdrawn from where it is necessary to retreat (Donetsk and Luhansk). The Russian - Ukraine war can be considered a multi-dimensional disaster, which is likely to get much worse in the foreseeable future because while a war is successful, little attention is paid to its causes, but when the outcome is disastrous, understanding how it happened becomes paramount. All in all, this study intends to provide an overview of the Russia-Ukraine war and its causes with Waltz's three Images as Individual, Domestic Politics, and international systems as well. In addition to this, it also has attempted to understand the long-term effect(s) on world politics as well.